2020
DOI: 10.1007/s42243-020-00469-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vanadium on hydrogen embrittlement susceptibility of high-strength hot-stamped steel

Abstract: Based on the chemical composition of traditional hot-stamped steel (e.g., 22MnB5 and 30MnB5), Nb and V microalloying elements are added into 30MnB5 steel to meet the requirements of ultra-high strength, excellent ductility and potent resistance to hydrogen embrittlement (HE) at the same time. The influence of hot-stamped steel on HE was studied by conducting a hydrogen permeation method and pre-charged hydrogen slow strain rate test. Meanwhile, the experimental steel microstructures and corresponding fracture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Other researchers [18][19][20] had also found that the addition of vanadium reduced the hydrogen diffusion coefficient as a result of vanadium precipitates as hydrogen traps. Obviously, these researchers did not consider the change of grain boundary character distribution (GBCD) could influence hydrogen diffusion behaviour when discussing the effect of vanadium content on hydrogen diffusion behaviour in tested steels.…”
Section: Introductionmentioning
confidence: 96%
“…Other researchers [18][19][20] had also found that the addition of vanadium reduced the hydrogen diffusion coefficient as a result of vanadium precipitates as hydrogen traps. Obviously, these researchers did not consider the change of grain boundary character distribution (GBCD) could influence hydrogen diffusion behaviour when discussing the effect of vanadium content on hydrogen diffusion behaviour in tested steels.…”
Section: Introductionmentioning
confidence: 96%
“…Effects of these microalloying elements mainly include solute drag, particle pinning, and precipitation strengthening [19]. Nevertheless, a further increase of microalloying elements failed to continuously enhance the strength [22,25,26] but significantly raised the cost of steels. This means that an optimised addition of microalloying elements needs to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al 9 found that the mechanical properties of hot stamping steel containing niobium were better than that of hot stamping steel without niobium, and the uniformity and fineness of microstructure were obviously improved. Lin et al 10,11 studied the effect of niobium content on the original austenite grain size of 22MnB5 and 38MnB5 hot formed steels.…”
Section: Introductionmentioning
confidence: 99%